Implementasi Pengembangan Kompetensi Aparatur Sipil Negara Satuan Pelayanan Terminal Tipe A Kertonegoro Ngawi Jawa Timur - Toyibi, Toyibi; Nugroho, Rino Ardhian; Mulyadi, Asal Wahyuni Erlin (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The development of civil servant (ASN) competencies at the Service Unit (Satpel) of Type A Kertonegoro Terminal in Ngawi aims to enhance professionalism in public service, particularly in land transportation, and to improve the terminal's operational management system. However, the implementation of competency development in the field often faces various challenges. This study explores the implementation of ASN competency development at the Type A Kertonegoro Terminal and the factors influencing its execution. This research uses a qualitative descriptive method, which seeks to explain phenomena in depth through data collection techniques such as interviews and document analysis. The data obtained were analyzed through three stages: data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of competency development at the Satpel of Type A Kertonegoro Terminal has not yet reached optimal levels. Several influencing factors include: first, internal communication tends to be one-way and directive, failing to accommodate employees’ aspirations for skill development; second, limited human resources in terms of both quantity and quality; third, low employee motivation to improve competencies through formal education due to the rotating work schedule (24 hours on, 24 hours off), which makes it difficult to balance education, work, and family responsibilities; and fourth, the Satpel Terminal is not authorized to manage its own budget, which diminishes motivation for competency development. To address these issues, the East Java Land Transportation Management Center (BPTD), as the parent office overseeing the Kertonegoro Terminal Satpel, has undertaken several initiatives. These include establishing collaborations with educational institutions, preparing annual plans for competency development needs, nominating staff for available training programs, and encouraging proactive participation in online training sessions.